Infection prevention control and organisational patient safety culture within the context of isolation: study protocol - John Gammon; Julian Hunt; Sharon Williams; Sharon Daniel; Sue Rees; Sian Matthewson (BMC, 2019)
Abstract Background Healthcare associated infection (HCAI) is a major cause of morbidity and mortality. In recent years, there have been high profile successes in infection prevention control (IPC), such as the dramatic reductions in methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections (which is viewed as one proxy indicator of overall harm) and Clostridium difficile in the UK. Nevertheless, HCAI remains a costly burden to health services, a source of concern to patients and the public and at present, is receiving priority from policy makers as it contributes to the global threat of antimicrobial resistance. Methods The study involves qualitative case studies within isolation settings at two National Health Service (NHS) district general hospitals (DGHs) in Wales, in the UK. The 18-month study incorporates Manchester Patient Safety Framework (MaPSaF) workshops with health workers and other hospital staff, in depth interviews with patients and their relative / informal carer, health workers and hospital staff, and periods of hospital ward observation. Discussion The present study aims to investigate the ways in which engagement of health workers with IPC strategies and principles, shape and inform organisational patient safety culture within the context of isolation in surgical, medical and admission hospital settings; and vice-versa. We want to understand the meaning of IPC 'ownership' for health workers; the ways in which IPC is promoted, how IPC teams operate as new challenges arise, how their effectiveness is assessed and the positioning of IPC within the broader context of organisational patient safety culture, within hospital isolation settings.